Chances and challenges for the members of the Fairtrade-supply chain: a case study of Chile and Switzerland - Regina Maria Martha Förg (Junior Management Science (JUMS), 2023)
Conventional international trade has become discredited because of emerging conflicts on fairness on producers' economic, social & ecological situation. Aiming to provide alternatives, the Fairtrade-certification was amongst the first that incorporated solidarity within the worldwide economy. Within a few decades the certification managed to exceed its pure labelling activities and implemented a whole supply chain, representative for debates about due diligence in international supply chains. While such a partnership is vital for more fairness in supply chains, it poses challenges to its agents. This paper, based on a case study of Swiss and Chilean companies, aims to explore the complexity for members in such a Fairtrade-supply chain. To this effect, it sheds light on the social and economic chances and challenges both for producers and merchandisers participating in the Fairtrade-system. The study gives evidence that this supply chain is a cooperation on eye-level which can provide an alternative to conventional free trade. Further, it shows that motivation and cultural background play a decisive role in the chances and challenges of Fairtrade-members. Ultimately, it proves that Fairtrade can be a partner for rising legal requirements in the course of due diligence laws.
Keywords: 650; CSR; Case study; Fairtrade; Supply chain; Due diligence